INTERAKSI SOSIAL ASOSIATIF DALAM BENTUK KERJASAMA ANTAR SUKU DAYAK RIBUN DAN JAWA - Ria, Hildegardis; Aminuyati, Aminuyati; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to describe associative social interactions in the form ofcooperation between the Dayak Ribun and Javanese people at Kelompu Villageneighborhood one, Kembayan sub-district of Sanggau Regency. The focus of thisresearch was the discussion of harmony in cooperation, driving factors for thecommunity"™s willingness to work together, and the social value that thecommunity gets from the cooperation. This study used a qualitative approachwith a descriptive method. The data collection techniques used were observation,interviews, and documentation. In addition, the techniques of data analysis usedwere data reduction, data display, as well as conclusion or verification. Thefindings showed that the harmony between the ethnics appeared in theircooperation and when they help each other. Factors that drive the community"™swillingness to work together were their common interests, awareness, andsanction. Social values obtained from their cooperation were unity, kinship,responsibility, tolerance, as well as harmony.Keywords: Ethnics, Community, Cooperation, Social Interaction, Social Values.